Color-selective printed organic photodiodes for filterless multichannel visible light communication - Strobel, Noah; Droseros, Nikolaos; Köntges, Wolfgang; Seiberlich, Mervin; Pietsch, Manuel; Schlißke, Stefan; Lindheimer, Felix; Schröder, Rasmus R.; Lemmer, Uli; Pfannmöller, Martin; Banerji, Natalie; Hernandez‐Sosa, Gerardo (Advanced materials, 2020)
Future lightweight, flexible, and wearable electronics will employ visible-light-communication schemes to interact within indoor environments. Organic photodiodes are particularly well suited for such technologies as they enable chemically tailored optoelectronic performance and fabrication by printing techniques on thin and flexible substrates. However, previous methods have failed to address versatile functionality regarding wavelength selectivity without increasing fabrication complexity. This work introduces a general solution for printing wavelength-selective bulk-heterojunction photodetectors through engineering of the ink formulation. Nonfullerene acceptors are incorporated in a transparent polymer donor matrix to narrow and tune the response in the visible range without optical filters or light-management techniques. This approach effectively decouples the optical response from the viscoelastic ink properties, simplifying process development. A thorough morphological and spectroscopic investigation finds excellent charge-carrier dynamics enabling state-of-the-art responsivities >102 mA W−1 and cutoff frequencies >1.5 MHz. Finally, the color selectivity and high performance are demonstrated in a filterless visible-light-communication system capable of demultiplexing intermixed optical signals.